Single-chain antibodies as diagnostic tools and therapeutic agents - Hagemeyer, Christoph E.; Muhlen, Constantin von zur; Elverfeldt, Dominik von; Peter, Karlheinz (Thrombosis and Haemostasis, 2009)
Over three decades after the generation of the first mouse monoclonal antibodies by Kohler and Milstein, recombinant antibodies are the fastest growing class of therapeutic proteins. Furthermore, antibodies are key detection reagents in research and diagnostics. Technology improvements have provided several approaches to manufacturing human antibodies with high affinity for biologically relevant targets. Approximately 300 development programs for therapeutic antibodies have been reported in industrial and academic laboratories, and this clearly demonstrates the expectations towards antibody technology. Antibody fragments are a subclass with growing clinical importance. This review focuses on single-chain antibodies as one of the smallest possible format for recombinant antibodies and their use as diagnostic tools and therapeutic agents. We describe the structure, selection and production of single-chain antibodies. Furthermore, we review current applications of antibody fragments focusing on thrombus targeting using fibrin- and platelet-specific single-chain antibodies as well as describing novel noninvasive imaging approaches for the diagnosis of thrombosis and inflammation.
Keywords: Antibody fragments; imaging; thrombosis; inflammation; phage-display